Ghanaian Clay as a Catalyst for Transesterificating Shea Butter Oil as Alternative Feedstock for Green Energy Production - Mohammed Takase (International Journal of Chemical Engineering)
In this study, catalytic transesterification of Shea butter oil with methanol to biodiesel was carried out. The clay particle was first sieved with a 250 ml sieve and then calcined at 800μC for 8 hours in a furnace. The calcined clay was then modified with 5% each of Zn(NO3)2 and SnCl2 separately for 3 h at 60°C using incipient wetness impregnation method. The slurry compositions were then dried at 120°C overnight in an oven. The modified clay catalysts were subsequently calcined for 3 hours at 600°C. The clay that had been modified with SnO2 and ZnO was assigned SD and ZD, respectively, whereas the clay that had not been doped (control) was assigned as AC. The catalysts were characterized using X-ray Diffractometer (XRD), Brunauer Emmett Teller (BET) surface area, and Scanning Electron Microscopy (SEM). Biodiesel was then produced from each of the catalysts under varying conditions of methanol to oil molar ratio, catalyst concentration, reaction temperature, and reaction time. When compared the performances of the catalysts (activated clay modified with SnO2, ZnO, and the control), activated clay modified with SnO2 resulted in an optimal conversion yield of 99.8% under 8 : 1 methanol to oil molar ratio, 1% catalyst concentration, 60°C of reaction time in 60 minutes. The catalytic performance was affected by the basicity and surface area of the catalysts. The biodiesel produced was comparable to American and European Union standards.